Effect of fatigue on the movement activities of senior male Zimbabwean national rugby sevens players - van den Berg, P. H.; Malan, D. D. J.; de Ridder, J. H. (International Journal of Performance Analysis in Sport, 2017)
The objective of the study was to determine the effect of fatigue on the percentage of time sevens rugby players spend on the movement activities during the two different halves of match play and to compare the percentage of time starter and substitute players spend on high and low-intensity movement activities. Sixty-one time-motion analyses data-sets of twelve (12) senior male elite Zimbabwean rugby sevens players with a mean age of 27.8 years were gathered at two International Sevens rugby tournaments. Time-motion analysis data were captured at 10 Hz with a minimaxX GPS device. Results indicated that starter players covered a significantly greater distance (r = 0.26) than substitute players. However, substitute players covered a significantly greater relative distance (distance per minute) (r = 0.33) than the starter players. Hence, the substitute players had less rest during match play and therefore a higher work-to-rest ratio than the starter players. No large practically significant differences found between the high intensity movement activities of the players during the two halves of match play, suggesting that fatigue did not affect the players` movement activities. The results therefore suggest that the use of substitute players may support the ability of teams to increase the players work rate.